Concept of Accounting Information System and Management Control System to Improve Company Performance - Fella Yunita Fitriyani (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2019)
Accounting information systems (AIS) are collections of activities from organizations that are responsible for providing financial information obtained from data transactions for computer-based reporting purposes. So an accounting information system (AIS) is part of a Management Information System (MIS) that is responsible for financial statements and data transactions. Whereas the Management Control System (MCS) is a system used by management including methods, procedures, and strategies to collect, analyze information, evaluate and use it, as well as other actions to exercise control. The explanation above shows that information (accounting information and additional information) is needed by management to control in the company. This study provides a concept regarding Accounting Information Systems, Management Control Systems, and Company Performance. When the management control process is right, then the company's performance in increasing management control systems can provide information in an adequate communication structure so that it can be used as a basis for decision making. Decision making supported by accurate information makes the performance of unit managers able to take anticipatory steps and improve operational efficiency and effectiveness so that the performance of unit managers will be improved.